2020
DOI: 10.1016/j.diabres.2020.108454
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with type 2 diabetes with and without Covid-19: A case control study (CoViDiab I)

Abstract: Aims To evaluate whether subjects with diabetes hospitalized for Coronavirus disease-19 (Covid-19) represent a subgroup of patients with high-risk clinical features compared to patients with diabetes without Covid-19. Methods In this case-control study 79 patients with type 2 diabetes out of 354 adults hospitalized for Covid-19 and 158 controls with type 2 diabetes but without Covid-19, matched for age and gender, were enrolled. Medical history and concomitant therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 34 publications
1
34
1
2
Order By: Relevance
“…The Covid-19 & Diabetes (CoViDiab) study is a multicenter observational study which collected data retrospectively from medical charts of patients hospitalized for Covid-19 from March 1 st to May 15 th , 2020 in four academic hospitals located in the Lazio region of Italy: Umberto I "Policlinico" General hospital and Sant' Andrea hospital, Sapienza University of Rome; Santa Maria Goretti hospital, Polo Pontino of Sapienza University in Latina; Campus Bio-Medico University hospital in Rome [23]. Patients eligible for inclusion were aged ≥ 18 years old with a diagnosis of Covid-19 confirmed by at least one real-time polymerase chain reaction assay, in accordance with the protocol established by the World Health Organisation [24].…”
Section: Study Design and Populationmentioning
confidence: 99%
“…The Covid-19 & Diabetes (CoViDiab) study is a multicenter observational study which collected data retrospectively from medical charts of patients hospitalized for Covid-19 from March 1 st to May 15 th , 2020 in four academic hospitals located in the Lazio region of Italy: Umberto I "Policlinico" General hospital and Sant' Andrea hospital, Sapienza University of Rome; Santa Maria Goretti hospital, Polo Pontino of Sapienza University in Latina; Campus Bio-Medico University hospital in Rome [23]. Patients eligible for inclusion were aged ≥ 18 years old with a diagnosis of Covid-19 confirmed by at least one real-time polymerase chain reaction assay, in accordance with the protocol established by the World Health Organisation [24].…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Significantly, Maddaloni et al suggested an increased prevalence of COPD and of chronic kidney disease (CKD) in Covid-19 patients with diabetes (6).…”
Section: Worse Outcomes In Covid-19 Patients Affected By Obesity and mentioning
confidence: 99%
“…However, COPD did not remain independently associated with hospitalization risk. Conversely, the CoViDiab I and II studies showed that COPD was significantly associated with a higher risk of both COVID-19 hospitalization and progression towards bad outcomes [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemic of coronavirus disease 2019 (COVID- 19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), reported in Wuhan, China in December 2019, before rapidly spreading worldwide. Pandemic status was declared by the World Health Organization in March 2020 [1].…”
Section: Introductionmentioning
confidence: 99%